Strategi Komunikasi Code Switching oleh Pembelajar Bahasa Inggris Sebagai Bahasa Asing - Fauziati, Endang - (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2020)
This qualitative study aims to examine the types and realization of the use of Code Switching communication strategies used by junior high school students when communicating in English as a foreign language. The research subjects were 30 students of SMP N IV Surakarta. The research objects were the types and realization of the use of code switching communication strategies used by students when communicating in English. Data were collected through the elicitation technique in which the participants were given the task to describe a cartoon; their speech was recorded and used as the data source. The data were analyzed qualitatively by inductive techniques using Dornyei and Myers-Scotton analysis frameworks. Research findings were interpreted by using relevant theory. The results showed that the learners used three types of code switching, namely: tag code switching, intra sentential code switching, and inter-sentential code switching. And there were three factors that contributed to the use of code switching, namely mastery of bilingual or bilingual, limited mastery of English, and as a compensation strategy. It can be concluded that the use of code switching by English learners as a foreign language is a natural and unavoidable. Because code switching is one of the communication strategies to compensate for the limited mastery of the target language.